To Better Generate Organoids, What Can We Learn From Teratomas? - Li, Hongyu; Gao, Lixiong; Du, Jinlin; Ma, Tianju; Ye, Zi; Li, Zhaohui (Frontiers in Cell and Developmental Biology, 2021)
The genomic profile of animal models is not completely matched with the genomic profile of humans, and 2D cultures do not represent the cellular heterogeneity and tissue architecture found in tissues of their origin. Derived from 3D culture systems, organoids establish a crucial bridge between 2D cell cultures and in vivo animal models. Organoids have wide and promising applications in developmental research, disease modeling, drug screening, precision therapy, and regenerative medicine. However, current organoids represent only single or partial components of a tissue, which lack blood vessels, native microenvironment, communication with near tissues, and a continuous dorsal-ventral axis within 3D culture systems. Although efforts have been made to solve these problems, unfortunately, there is no ideal method. Teratoma, which has been frequently studied in pathological conditions, was recently discovered as a new in vivo model for developmental studies. In contrast to organoids, teratomas have vascularized 3D structures and regions of complex tissue-like organization. Studies have demonstrated that teratomas can be used to mimic multilineage human development, enrich specific somatic progenitor/stem cells, and even generate brain organoids. These results provide unique opportunities to promote our understanding of the vascularization and maturation of organoids. In this review, we first summarize the basic characteristics, applications, and limitations of both organoids and teratomas and further discuss the possibility that in vivo teratoma systems can be used to promote the vascularization and maturation of organoids within an in vitro 3D culture system.